Bilingual Color Learning Application as Alternative Color Learning for Preschool Student - Istiono, Wirawan (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Color recognition skills for early childhood are very important as a basis for starting other learning, by recognizing colors a child will get the benefits of creative development, development of sensory abilities and other positive benefits. Based on the results of observations that had been done in the kindergarten school that locate in Tangerang, Indonesia, it was found that most children were still often confused or had difficulty distinguishing colors through conventional teaching. In this research, a color recognition application was built in two languages, which aims to help students to recognize color faster. Testing will be carried out using the pretest and posttest methods with the "paired sample t test" method to measure the level of student development before and after using the application, user acceptance testing will also be carried out using UAT to measure the level of user acceptance of the application that had been made. From these evaluation, it was found that the results of the development were quite good with the t-stat results of 8.69 and the user acceptance test results of 86.72%.